Homocysteic acid in blood can detect mild cognitive impairment (MCI) and MCI due to Alzheimer disease (AD) pathological change: Biomarkers (non‐neuroimaging) / plasma/serum/urine biomarkers. (7th December 2020) - Hasegawa, Tohru; Kosoku, Yoshinori; Sano, Yuka; Yoshida, Hiroshi; Kudoh, Chiaki; Tabira, Takeshi
Abstract: Background: Recent our findings present a new early diagnostic marker for mild cognitive impairment (MCI), a pre‐stage of Alzheimer's disease (AD). It may be a causative substance of AD and a therapeutic target. In the treatment of AD, it is thought to be most effective to intervene at the earliest and mildest stages. So it is desirable to use a biomarker that can be detected by a minimally invasive, cost‐effect technique. Method: The participants of our study were between 60 to 90 years. The data set consisted of 12 participants with AD, 12 with MCI, and 9 cognitively normal individuals as Negative Control (NC) (33 in total).The study was approved by the research ethics committee of Kudoh Chiaki Neurosurgery Clinic. In the study, we measured TNF‐α, cortisol and ACTH by ELISA, and measured HCA, tau and phosphorylated tau by CLEIA. Result: We evaluated which items were useful as diagnostic markers for MCI and AD by Receiver Operating Characteristic (ROC) analysis. In ROC analyses, for distinguishing diagnostic markers between NC and MCI, the ROC curve of HCA showed very high areas under the ROC curves (AUC). When 0.116 μM of HCA is chosen as the cut‐off, the sensitivity is 91.7% and the specificity is 77.8 %. In our results, the item of HCA was the most useful as a diagnostic marker for MCI. In ROC analyses, in distinguishing diagnostic markers between MCI and AD, the ROC curve of tau and p‐tau showed a very high AUC. When 17.0 pg/mL of tau and 5.9 pg/mL of p‐tau are chosen as the cut‐off, the sensitivity is 83.3%, 91.7% and the specificity is 91.7%, 75.0%, respectively. Conclusion: Our results suggested that plasma HCA level is useful as early diagnostic markers of AD. This is because measured values of HCA increase in the stage of MCI, and are thus useful as a diagnostic marker for MCI. On the other hand, our results suggested that plasma tau and p‐tau are useful diagnostic markers for confirming disease progression, because their measured values are linked to cognitive decline and, thus, they are useful as diagnostic markers for AD.